"Diklastri" Model As Alternative to Improve the Quality of Vocational High School Graduates - Yoto Yoto (Universitas Negeri Malang, 2015)
Model "Diklastri" Sebagai Alternatif Meningkatkan Mutu Lulusan SMK   Abstract: Link and match policies implemented by SMK with various shapes and models. "Industrial Education Class " model is one form of manifestation of the link and match policy, which is a model of the implementation of vocational education is arranged and agreed upon by the school and industry. Students receive education in schools in the form of normative subjects, adaptive and basic vocational. While in industry, students working directly in the field carrying out appropriate jobs in the industry. Education system arranged in layers with the block system, planned, implemented, and supervised by the school and industry separately or together. This model combines the learning-oriented vocational training in schools and learning experiences related to working in the industry. Work learning experience provided to students must be in accordance with the program of study and career goals of students. The integration of vocational training in the school and experience working in the industry will form the character of students to be responsible, disciplined and enjoys the work, so that "Industrial Education Class" model able to improve the quality of vocational graduates. Key Words: industrial class, quality of graduates, SMK   Abstrak: Kebijakan link and match  dilaksanakan olek SMK dengan berbagai ragam bentuk dan model. Model "Pendidikan Kelas Industri" adalah salah satu bentuk perwujudan dari kebijakan link and match, yaitu suatu model pelaksanaan pendidikan kejuruan yang diatur dan disepakati oleh sekolah dan industri. Peserta didik  menerima pendidikan di sekolah berupa mata pelajaran normatif, adaptif dan dasar kejuruan. Sedangkan di industri peserta didik bekerja langsung di lapangan sesuai pekerjaan yang ada. Sistem pendidikan diatur secara berlapis dengan sistem blok, direncanakan, dilaksanakan dan disupervisi oleh sekolah dan industri secara terpisah atau bersama-sama. Model ini memadukan antara pembelajaran yang berorientasi pada latihan kerja di sekolah dan pengalaman belajar dengan bekerja di industri. Pengalaman belajar dan bekerja yang diberikan kepada peserta didik harus sesuai dengan program studi dan tujuan karir peserta didik. Keterpaduan pengalaman latihan kerja di sekolah dan bekerja di industri akan membentuk karakter peserta didik untuk bertanggung jawab, disiplin dan menyenangi pekerjaan, sehingga model "Pendidikan Kelas Industri" mampu me-ningkatkan mutu lulusan SMK.  Kata kunci: kelas industri, mutu lulusan, SMK